Rekomendasi Tempat Penyimpanan Sementara Limbah B3 (TPS LB3) PT X Industri Transportasi - Muchammad Kasyfurrahman Shidqi; Okik Hendriyanto Cahyonugroho (Jurnal Serambi Engineering, 2025)
The management of hazardous and toxic waste (B3 waste) is crucial in industrial sectors to prevent environmental damage and ensure the safety of humans and other living beings. This research focuses on the design and recommendation of a Temporary Storage Facility (TPS) for B3 waste at PT X, which operates in the transportation industry. The types of B3 waste identified include used oil, used rags, brake fluid, grease, and radiator water. Using a multi-method approach, the study used interviews, observations, and logbook analysis to determine the characteristics, quantities, and storage requirements of the waste. The research also adhered to Indonesian regulations to ensure compliance in waste management and storage. The recommended TPS design includes features such as proper ventilation, fire extinguishers, first aid kits, and labeling based on waste characteristics. Storage capacity calculations and layout have been optimized to match existing site conditions and ensure operational efficiency. The proposed TPS layout is expected to enhance workplace safety, minimize environmental contamination risks, and improve overall waste management practices at PT X.